(untitled) (Biological Sciences - PJSIR, 1999)
Gypsum occurs at four localities around Muzaffarabad i.e. Balak Bhanna, Sherwan, Shawai and Thangar areas between 2-4 kilometers northwest of Muzaffarabad, Azad Kashmir along the west bank of river Neelum and .Katha Shawai. This gypsum is fine-grained and massive and belongs to Hazara formation. The reserves are enough to be used in different industires. Samples were taken from these four deposits and studied for their commerical and industrial suitability for theproduction of gypsum plaster.The physical studies proved that "PIas- ter of Paris" produced from these samples conform to the standard specifications for gypsum plasters.